Study protocol: "Two Teachers": A randomized controlled trial investigating individual and complementary effects of teacher-student ratio in literacy instruction and professional development for teachers. (2017) - Solheim, Oddny Judith; Rege, Mari; McTigue, Erin
Highlights: Protocol for a RCT on effect of teacher-student ratio and professional development. Longitudinal intervention implemented in Literacy Instruction in Grade 1 through 4. Two tier treatment: 1) increased teacher-student ratio 2) professional development. Large population-based sample: 5843 students from 150 schools. Primary outcome data tracks student literacy skill and motivation. Abstract: This paper presents a research protocol for a randomized controlled trial investigating individual and complementary effects of teacher-student ratio and professional development for teachers. We do all effect analyses on the following domains of measures: (i) Students achievement in word reading, reading comprehension and spelling, (ii) Students' literacy interest, reader self-concept and achievement strategies, (iii) Classroom climate and emotional support (iv) Teaching practices in literacy instruction. 150 schools, with two classes per school, participate in the trial. We vary treatment in two tiers: 1) increased teacher-student ratio, and 2) adaption of a program that aims to facilitate the development of learning communities by inspiring teachers to reflect upon their practice and try out new, research-based methods for promoting children's literacy skills. The two-tiered design allows us to investigate effects of increased teacher-student ratio, effects of professional development, and importantly: complementary effects of these two treatments. This protocol details background, design, intervention, and outcome measures.